Knowledge and attitude regarding Pain management among nurses In acute care settings in Hospital Universiti Sains Malaysia - Rahim, Noriza Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Pain is very subjective that can affects everyday living through physical, emotional and spiritual and can significantly alter the quality of life. Due to the nature complex of pain, providing relief is a challenging task for healthcare provider. The role of nurses is important in the assessment and management of pain experienced by patients during hospitalization. Therefore, the purpose of this study was to determine the knowledge and attitude regarding pain management among nurses in acute care settings in Hospital Universiti Sains Malaysia, Kubang Kerian. A descriptive, cross-sectional design was used in this study. Data was collected using self administered questionnaire including demographics data and the Nurses' Knowledge and Attitudes Survey Regarding Pain (NKASRP). Seventy five nurses participate in this study. Data were analyzed using descriptive statistic and Chi-Square test. The average of correct response rate on NKASRP was 44.6%, ranging from 30% to 80%. Overall, majority of the respondents (93.3%) have low level of knowledge and attitudes regarding pain management. A Chi-Square test showed that there was significant association between duration of employment and level of knowledge and attitudes regarding pain management among nurses in acute care settings in HUSM (p=O.OOI). The result of this study revealed that the problem of knowledge and attitude deficit regarding pain management among nurses in acute care settings is alarming. Thus, basic and continuing education programs should be implement to improve the level of knowledge and attitude among them.